2020
DOI: 10.3390/ma13225127
|View full text |Cite
|
Sign up to set email alerts
|

Are Single Polymer Network Hydrogels with Chemical and Physical Cross-Links a Promising Dynamic Vibration Absorber Material? A Simulation Model Inquiry

Abstract: Tough, doubly cross-linked, single polymer network hydrogels with both chemical and physical cross-links display a high loss factor of the shear modulus over a broad frequency range. Physically, the high loss factor is resulting from the intensive adhesion–deadhesion activities of the physical cross-links. A high loss factor is frequently required by the optimization processes for optimal performance of a primary vibration system while adopting a dynamic vibration absorber, in particular while selecting a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…Equations ( 35 ) and ( 36 ) can be numerically implemented through a convolutional approach where both the history of stress and strain are needed [ 70 ]. More details regarding fractional integrals can be found in Lubich [ 71 ]; Kempfle et al [ 72 ]; Wang and Kari [ 39 ]; Alotta et al [ 70 ]; Kari [ 73 , 74 ]. It should be noted that a direct calculation of the Mittag–Leffler function in Equation ( 36 ) is not suggested.…”
Section: Particularization Of the Constitutive Modelmentioning
confidence: 99%
“…Equations ( 35 ) and ( 36 ) can be numerically implemented through a convolutional approach where both the history of stress and strain are needed [ 70 ]. More details regarding fractional integrals can be found in Lubich [ 71 ]; Kempfle et al [ 72 ]; Wang and Kari [ 39 ]; Alotta et al [ 70 ]; Kari [ 73 , 74 ]. It should be noted that a direct calculation of the Mittag–Leffler function in Equation ( 36 ) is not suggested.…”
Section: Particularization Of the Constitutive Modelmentioning
confidence: 99%
“…From Equation (1), it can be observed that the modulus magnitude bω a increases with increasing frequency and the loss factor tan (aπ/2) is a constant value for the fractional derivative element. For more details regarding the fractional derivative model, please refer to Lubich (1986), Lion and Kardelky (2004), and Kari (2017Kari ( , 2020.…”
Section: Constitutive Modelingmentioning
confidence: 99%
“…Further, scholars have adopted the variable stiffness material as a spring element at present. The shape memory alloy, a linear spring, and hydrogels [13][14][15] usually serve as the spring element, because their stiffness is regulatable under external excitations. These DVAs are classified as active vibration absorbers.…”
Section: Introductionmentioning
confidence: 99%